Pelatihan Gerabah Dalam Mendorong Regenerasi Pengrajin Sebagai Upaya Penguatan Ekonomi Kreatif di Desa Sumber Kemuning, Kecamatan Tamanan, Kabupaten Bondowoso - Alfisyah Nurhayati; Achmad Reynaldi Valentino; Hendi Yoga Pratama; Muhammad Rizki Hafianto Putra; Desy Adellia Jovanka; Komariyatul Hasanah; Pinastika Rafikayati; Ayyul Fariqoini; Niken Nurazizah Maharani; Silna Shohabah; Nur Juwita Sari; Adila Fithriyya Afkarina; Lidiana Febriyanti; Hilma Fitriatuzzuhria; Fika Rohmatul Ainiyah; Alifya Nur Salsabila (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Krajan Hamlet, Sumber Kemuning Village, Bondowoso Regency, is a pottery craft center that holds cultural value and creative economic potential. However, it is currently facing a serious challenge, namely the lack of artisan regeneration due to the shifting interests of the younger generation. This community service activity aims to encourage artisan regeneration through pottery training as a strategy for cultural preservation as well as strengthening the creative economy based on local wisdom in Sumber Kemuning Village. The method employed in this program is Participatory Action Research (PAR), involving the community, pottery artisans, village youth, and village officials. The program was carried out through several stages, including surveys and observations, Focus Group Discussions (FGD), socialization, training, and evaluation. The results of the activity indicate an improvement in technical pottery-making skills, participants’ understanding of the economic value embedded in pottery crafts and cultural traditions, as well as the growing awareness of the younger generation to take part in preservation efforts. Participants were also equipped with digital marketing strategies to expand market access for their enterprises. Thus, this training program has proven effective in addressing the challenge of artisan regeneration and has the potential to serve as a replicable empowerment model in other regions with similar conditions.